Clinical characteristics and natural history of wild‐type transthyretin amyloid cardiomyopathy in Japan - Yamada, Toshihiro (ESC Heart Fail, 2020)
AIMS: The focus on wild‐type transthyretin amyloid cardiomyopathy (ATTRwt‐CM) is increasing because of novel treatment options. There is currently no report on a large number of Japanese patients with ATTRwt‐CM. The study aimed to examine the characteristics and prognosis of ATTRwt‐CM in Japan. METHODS AND RESULTS: Consecutive patients (78.5 ± 6.4 years old at diagnosis) with ATTRwt‐CM diagnosed at Kumamoto University Hospital between December 2002 and December 2019 were retrospectively reviewed. Data, including demographic characteristics, co‐morbidities, clinical manifestations at diagnosis, laboratory results, electrocardiographic and echocardiographic data, imaging and pathological findings, and treatment were obtained. Of 129 patients included in this study, 110 patients (85%) were male. The median period from initial symptom onset to diagnosis was 15.5 (2–75) months. Heart failure was the most common clinical manifestation leading to diagnosis (61%) and initial manifestations (49%). Of 106 patients, carpal tunnel syndrome was observed in 57 patients (54%), and the median period from initial symptom onset to diagnosis was 96 (48–120) months. Histopathological confirmation of transthyretin amyloid was achieved in 94 patients (73%), including 66 (51%) and 28 cases (22%) with endomyocardial and extracardiac biopsies. During the observation period (median 15.0 [inter‐quartile range, 5.4–33.2] months after diagnosis), 34 patients (26%) died. Of these, 27 patients (79%) had cardiovascular deaths (heart failure, 25; sudden death, two). The median survival duration was 58.9 months and the 5 years' survival rate was 48%. According to a multivariate Cox hazard analysis, age [hazard ratio (HR), 1.14; 95% confidence interval (CI), 1.05–1.23, P = 0.002] and low serum sodium levels (HR, 0.89; 95% CI, 0.79–0.996; P = 0.04) contributed to all‐cause mortality, and low serum sodium levels contributed to hospitalization for heart failure (HR, 0.86; 95% CI, 0.77–0.96; P = 0.005). CONCLUSIONS: Clinical characteristics and prognosis of ATTRwt‐CM patients in Japan were examined. Carpal tunnel syndrome can be considered an indication for diagnosis of ATTRwt‐CM. Age and low serum sodium level were significant predictive factors of all survival outcomes. The clinical features of ATTRwt‐CM should be recognized to provide appropriate treatment.